2019
DOI: 10.1029/2018tc005346
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Implications of Sediment Transport for the Architecture and Evolution of Continental Rifts and Margins

Abstract: Erosion and deposition redistribute mass as a continental rift evolves, which modifies crustal loads and influences subsequent deformation. Surface processes therefore impact both the architecture and the evolution of passive margins. Here we use coupled numerical models to explore the interactions between the surface, crust, and lithosphere. This interaction is primarily sensitive to the efficiency of the surface processes in transporting mass from source to sink. If transport is efficient, there are two poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 92 publications
10
56
0
Order By: Relevance
“…Our models show symmetric margins similarly to Theunissen and Huismans () but in contrast to models from Brune et al () and Andrés‐Martínez et al (). Huismans and Beaumont () showed that the large‐scale asymmetry observed in numerical models is likely the result of feedback between the dominant rheology (in a layered lithosphere context) and the parameterization of the strain softening.…”
Section: Discussionsupporting
confidence: 61%
“…Our models show symmetric margins similarly to Theunissen and Huismans () but in contrast to models from Brune et al () and Andrés‐Martínez et al (). Huismans and Beaumont () showed that the large‐scale asymmetry observed in numerical models is likely the result of feedback between the dominant rheology (in a layered lithosphere context) and the parameterization of the strain softening.…”
Section: Discussionsupporting
confidence: 61%
“…A linear relationship has been established between P wave velocities and volume percent serpentine in peridotites (Carlson & Miller, ; Christensen, ; O'Hanley, ). In particular, the correlation at 200 MPa and 200 °C of Christensen () closely approximates the conditions expected along the Galicia crust‐mantle boundary during rifting (Andrés‐Martínez et al, ). This correlation was utilized to convert the mantle velocities (supporting information Text S2) presented in Schuba et al () into a map of mantle serpentinization beneath the S‐reflector detachment fault (Figure ).…”
Section: Methodssupporting
confidence: 73%
“…Erosion and sedimentation have been shown to enhance the lifespan of individual normal faults in numerical simulations (Olive et al, 2014;Andrés-Martínez et al, 2019; Theunissen and Huismans, 2019). Olive et al (2014) attributed this effect to surficial mass redistribution alleviating the energy cost of topography buildup.…”
Section: Discussionmentioning
confidence: 99%
“…Tectonic models commonly predict that erosion and sedimentation enhance strain localization onto a few major faults at subaerial plate boundaries such as orogens (e.g., Masek and Duncan, 1998;Willett, 1999) and continental rifts (Olive et al, 2014;Andrés-Martínez et al, 2019;Theunissen and Huismans, 2019). By contrast, the influence of seafloor-shaping processes on the tectonic makeup of submarine boundaries has received far less attention, possibly because erosion is commonly considered highly inefficient in the deep ocean.…”
Section: Introductionmentioning
confidence: 99%